ЦИФРОВАЯ ТРАНСФОРМАЦИЯ УНИВЕРСИТЕТСКИХ БИБЛИОТЕК В КОНТЕКСТЕ УСТОЙЧИВОГО РАЗВИТИЯ - Яхьяева Дилорам Абидовна (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
The digital transformation of libraries is a key factor in ensuring the sustainable development of modern society. This article analyzes the main areas of digital innovation in university libraries, as well as the challenges arising in the implementation of digital technologies. The study is based on a qualitative method, including interviews with library staff and users, as well as an analysis of institutional documents. The results demonstrate that digital services contribute to expanding access to knowledge and reducing educational inequality. However, infrastructural limitations, insufficient digital literacy, and financial barriers significantly hinder the potential of digital libraries. This article concludes that a comprehensive approach to the digital development of libraries is necessary within the framework of implementing the Sustainable Development Goals.